2021
DOI: 10.3390/inorganics9070056
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metal Halide Perovskites as Photocatalysts in Organic Reactions

Abstract: This review summarizes the current status of the application of metal halide perovskites (MHPs) as photocatalysts in organic syntheses/transformations. It is shown that the optimal and unique electronic properties of MHPs can be advantageously used in several reaction types providing pros with respect to traditional photocatalysts. While still being at infancy, such field of application of MHPs as effective photocatalysts will for sure become a central research topic in the forthcoming years, thanks also to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…[93,99] Several organic transformations can be carried out under visible light in presence of lead halide perovskites as photocatalysts. [100,101] Lead halide perovskites also find applications in the field of photocatalytic degradation of persistent toxic organic compounds in polluted water. [91,102] The halide ion vacancy in the surface of the lead halide perovskites are known to enhance the photocatalytic property.…”
Section: Applicationsmentioning
confidence: 99%
“…[93,99] Several organic transformations can be carried out under visible light in presence of lead halide perovskites as photocatalysts. [100,101] Lead halide perovskites also find applications in the field of photocatalytic degradation of persistent toxic organic compounds in polluted water. [91,102] The halide ion vacancy in the surface of the lead halide perovskites are known to enhance the photocatalytic property.…”
Section: Applicationsmentioning
confidence: 99%
“…, CsPbX 3 (X = I, Br, Cl)) and polymers have been established as photocatalysts so far. 13 Recently, oxyhalide and metal oxyhalide compounds have been shown as potential photocatalysts, e.g. , Bi 2 MO 4 Cl (M = Y/La/Bi), PbBiO 2 X, Bi 12 O 17 Cl 2 , Bi 3 O 4 Cl, Bi 24 O 31 Cl x Br 10− x , PbBiO 2 Br/BiOBr, PbBiO 2 Br/UiO-66-NH 2 (mpg-C 3 N 4 /PbBiO 2 Br), Bi 4 NbO 8 Cl, Bi 24 O 31 Cl 10 .…”
Section: Introductionmentioning
confidence: 99%
“…), metal halide perovskites (MHP) (e.g., CsPbX 3 (X ¼ I, Br, Cl)) and polymers have been established as photocatalysts so far. 13 Recently, oxyhalide and metal oxyhalide compounds have been shown as potential photocatalysts, e.g., Bi 2 MO 4 Cl (M ¼ Y/La/Bi), PbBiO 2 X, Bi 12 O 17 Cl 2 , Bi 3 O 4 Cl, Bi 24 O 31 Cl x Br 10Àx , PbBiO 2 Br/BiOBr, PbBiO 2 Br/UiO-66-NH 2 (mpg-C 3 N 4 /PbBiO 2 Br), Bi 4 NbO 8 Cl, Bi 24 O 31 Cl 10 . 1,2,5,[14][15][16] Visible light responsive photocatalysis is responsible for the photocatalyzed decolorization of a dye in solution via a photoexcitation process.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 TiO 2 sensitized with halide perovskite QDs has been applied in visible-light-driven photocatalysis. 19 − 24 Schünemann et al reported the use of a CsPbBr 3 /TiO 2 composite for visible-light-driven photocatalytic benzyl alcohol oxidation. 19 Guo et al investigated a CsPbBr 3 /TiO 2 photocatalyst for visible-light photodegradation of rhodamine with better efficiency than a commercially available TiO 2 catalyst (P25) used as the reference material.…”
Section: Introductionmentioning
confidence: 99%